The influence of online customer reviews on brand attitudes and repurchase intentions in e-commerce in China - Zhang, Tianyang; Lee, Khai Loon; Puteri Fadzline, Muhamad Tamyez (Secholian Publication, 2025)
Online customer reviews (OCRs) play a pivotal role in shaping consumer behavior in the e-commerce landscape, particularly in China, where digital platforms dominate retail. This study explores the influence of OCRs on brand attitudes and repurchase intentions through a qualitative approach, utilizing in-depth interviews with e-commerce consumers. The findings reveal that the credibility and trustworthiness of OCRs, shaped by factors such as verified purchases, visual evidence, and detailed content, significantly impact consumer perceptions of brands. Positive reviews enhance trust and loyalty, while negative reviews have a stronger deterrent effect on repurchase intentions, particularly when corroborated by multiple sources. Emotional engagement with OCRs emerged as a critical mechanism, with relatable and detailed reviews resonating more profoundly with consumers. Cultural factors, including collectivist values and the integration of social media with e-commerce platforms, amplify the influence of OCRs by fostering community validation and social proof. The study highlights the importance of active review management for brands, emphasizing strategies such as encouraging authentic and detailed reviews, addressing negative feedback constructively, and leveraging social media to build trust and loyalty. These findings offer valuable insights for e-commerce businesses aiming to enhance customer engagement and drive repeat purchases in a competitive digital market. Future research is recommended to explore the integration of advanced technologies, such as AI, to further optimize the effectiveness of OCRs.